Observation of Atmospheric Water Vapors Using AIRS - Jihyun Ha; Dusik Kim; Kwan-Dong Park; Jihye Won (Journal of Astronomy and Space Sciences, 2009)
The Atmospheric Infrared Sounder (AIRS) aboard the Aqua satellite, which is one of the Earth Observing System satellites managed by National Aeronautics and Space Administration, provides global measurements of the water vapor in the atmosphere using infrared (IR) channels. In this paper, we restored precipitable water vapor (PWV) over a permanent GPS station in Incheon using the IR measurements of AIRS and compared the result with GPS-based PWV estimates. As a result, AIRS PWV had similar trends with GPS PWV; the bias of AIRS PWV against GPS PWV is 0.3 cm and root mean square error (RMSE) 0.7 cm. In addition, the correlation coefficient between AIRS PWV and GPS PWV was 0.89. Thus we conclude that the AIRS PWV reflects local characteristics of the water vapor content.